2019
DOI: 10.1039/c9tb01312a
|View full text |Cite
|
Sign up to set email alerts
|

Layered double hydroxide nanostructures and nanocomposites for biomedical applications

Abstract: Layered double hydroxide (LDH) nanostructures and related nanocomposites have attracted significant interest in biomedical applications including cancer therapy, bioimaging and antibacterial treatment.These materials hold great advantages including low cost and facile preparation, convenient drug loading, high drug incorporation capacity, good biocompatibility, efficient intracellular uptake and endosome/lysosome escape, and natural biodegradability in an acidic environment. In this review, we summarize the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(85 citation statements)
references
References 178 publications
3
82
0
Order By: Relevance
“…(4) The flexibility of manipulation on the nanometer scale of LDH-based nanocomposites is a superior advantage. This research field should be expanded, especially synergistic integration with various materials which can enhance the performance of LDH or complement the limitation of LDH nanostructures [71][72][73]. Here, we have described the interrelationship between the cytotoxicity and physicochemical properties of LDH nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…(4) The flexibility of manipulation on the nanometer scale of LDH-based nanocomposites is a superior advantage. This research field should be expanded, especially synergistic integration with various materials which can enhance the performance of LDH or complement the limitation of LDH nanostructures [71][72][73]. Here, we have described the interrelationship between the cytotoxicity and physicochemical properties of LDH nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to clay minerals, LDH matrices possess specific intrinsic properties such as anionic exchange, highly hydroxylated layers and biocompatibility, of great interest in various applications including catalysis, biology or coatings. 39,40 The synthesis of LDH-armored latex particles by Pickering emulsion polymerization could be an alternative way to obtain efficient dispersions of LDH platelets into polymer matrices and create new smart functional nanocomposite materials. Even if several authors have reported the formation of Pickering emulsions stabilized by LDH particles, [41][42][43][44] to the best of our knowledge no previous research has investigated the use of LDHs as Pickering stabilizers in emulsion polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33] Layered double hydroxides (LDHs) are well established as biocompatible nanocarriers of anionic drugs and biomolecules. [34][35][36][37] The structure of LDHs consists of the periodical stacking of positively charged metal hydroxide layers, typically containing divalent and trivalent metal cations, and negatively charged interlayers consisting of anions and water molecules. [38,39] LDHs possess valuable characteristics for use in biomedicine, such as low cytotoxicity, good biocompatibility and biodegradability, high drug loading, protection of drugs in the interlayer, and control of particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian cells internalize positively charged LDH nanoparticles very quickly via clathrin-mediated endocytosis. [37,40,41] The suitability of LDHs as hosts for molybdenum carbonyl complexes was demonstrated in three recent studies in which materials intercalated by the πallyl complex [Mo(η 3 -allyl)Cl(CO) 2 (bpdc)] 2-(bpdc = 2,2′-bipyridine-5,5′-dicarboxylate), the tetracarbonyl complex cis-[Mo(CO) 4 (bpdc)] and the cyclopentadienyl complex [CpMo(CO) 3 (CH 2 COO)]were prepared. [42][43][44] Exposure of the intercalated tetracarbonyl complex to visible light promoted decarbonylation, pointing to a possible application as a photoactivatable CORMA.…”
Section: Introductionmentioning
confidence: 99%